ANALISIS PENGEMBANGAN MEDIA PEMBELAJARAN PADA MATERI IPAS SEIRING BERJALANNYA WAKTU - Mahmada Assyifa; Martha Eka Ayu Pratiwi; Sulthan Ali Hakim; Surayanah Surayanah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study aims to analyze the evolution of instructional media in the IPAS subject in line with technological advancements, along with its impact on students’ conceptual understanding. A qualitative approach was employed using a literature review of scientific articles published between 2020 and 2025, sourced from Google Scholar and Garuda. Data analysis was conducted using content analysis techniques to identify types of instructional media and their influence on the IPAS learning process. The findings reveal a transformation of instructional media from conventional forms to digital and advanced technology-based formats, such as interactive applications, video animations, and augmented reality. These developments have a positive impact on improving students’ conceptual understanding, motivation, and engagement, particularly with abstract IPAS content. Technology-based media have proven to be more effective because they provide concrete and interactive visualizations. However, their implementation is still hindered by limitations in infrastructure and teacher skills. Therefore, it is necessary to strengthen teachers’ competencies in developing and utilizing innovative learning media to make IPAS learning more effective and meaningful.